The Weary Founder: Sleep Problems, ADHD-Like Tendencies, and Entrepreneurial Intentions. (January 2021) - Gunia, Brian C.; Gish, J. Jeffrey; Mensmann, Mona
Scholars have persuasively documented the positive influence of ADHD-like tendencies (the impermanent experience of ADHD-like symptoms) on entrepreneurial intentions. Yet, we know little about the causes of ADHD-like tendencies, and thus about factors that could heighten entrepreneurial intentions through such tendencies. Drawing from the biopsychosocial model, sleep physiology literature, and entrepreneurship literature, we propose that the biological experience of sleep problems may heighten the psychological experience of ADHD-like tendencies, which could nudge people toward the socially-embedded intention to venture. Four studies and a mini meta-analysis provide support, extending several literatures and suggesting that sleep problems could contribute to business founding.